Drone Untuk Deteksi Hama dan Penyemprotan Pestisida pada Tanaman Padi - Akhmad Taufik; Imran Habriansyah; Fachturrahman Fachturrahman; Hutomo F. R. Sumbung (Politeknik Negeri Ujung Pandang, 2022)
As the population increases, rice consumption will also increase. Therefore, the productivity of rice must be increased. However, the productivity of rice usually declines due to the brown planthopper. This study aims to create an image processing algorithm on a drone so that it can detect the color of rice leaves that are attacked by brown planthoppers and to create a mechanism for spraying insecticides. The methodology in this research begins with the design of mechanical and electronic systems on drones and spraying mechanisms, to the design of color detection programs and spraying mechanism programs. The testing of the spraying mechanism is carried out at various drone flight heights, ranging from Â±1 meter to Â±1.5 meters. The results of this study showed that the spraying mechanism was able to spray liquid and the image processing algorithm that had been made was able to detect brown rice leaf color and was able to spray liquid automatically when the color of the specified object was detected.